Real time voice recognition based smart home application - Bay?in, Mehmet; Karaköse, Mehmet (My University, 2012)
By the improvement of the technology, the applications used for simplifying the daily life create an important work area day after day. In this study, an equipment control component that could be used as intelligence home application based on voice recognition was improved. By this aim, database belonging to intended control voices like turn on the lamp, close the curtain was created by pre-processing the steps of the voice samples taken from five people. For education and test steps, the performance of the algorithm was compared by using Euclidian distance method, artificial neural network and dynamic time warping algorithm separately in the voice recognition step. As for the recognition step, the proposed algorithms were verified by the implementation of the duties that correspond to pairing words as real time on the control cards. © 2012 IEEE.
Gerçek zamanli ses tanima tabanli akilli ev uygulamasi
2012 20th Signal Processing and Communications Applications Conference, SIU 2012 -- 18 April 2012 through 20 April 2012 -- Fethiye, Mugla -- 90786
Keywords: Algorithms; Automation; Intelligent buildings; Neural networks; Signal processing; Control cards; Daily lives; Dynamic time warping algorithms; Equipment control; Euclidian distance; Home application; Pre-processing; Real time; Smart homes; Speech recognition